2020
DOI: 10.1155/2020/2642654
|View full text |Cite
|
Sign up to set email alerts
|

Families of Rational and Semirational Solutions of the Partial Reverse Space-Time Nonlocal Mel′nikov Equation

Abstract: Exact periodic and localized solutions of a nonlocal Mel′nikov equation are derived by the Hirota bilinear method. Many conventional nonlocal operators involve integration over a spatial or temporal domain. However, the present class of nonlocal equations depends on properties at selected far field points which result in a potential satisfying parity time symmetry. The present system of nonlocal partial differential equations consists of two dependent variables in two spatial dimensions and time, where the dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Both models can be viewed as complex reductions of the KPSCS (1.2). We have found that each short-wave packet f j 2 | | is actually characterized by an arbitrary function β j (t), which was never reported in the literatures on the research of the Mel'nikov model (1.1) and its extensions [1][2][3][4][22][23][24][25][26]. This b t j ( ) governs the effect of the shortwave packet and can bring more variety of interactions of line solitons.…”
Section: Discussionmentioning
confidence: 71%
“…Both models can be viewed as complex reductions of the KPSCS (1.2). We have found that each short-wave packet f j 2 | | is actually characterized by an arbitrary function β j (t), which was never reported in the literatures on the research of the Mel'nikov model (1.1) and its extensions [1][2][3][4][22][23][24][25][26]. This b t j ( ) governs the effect of the shortwave packet and can bring more variety of interactions of line solitons.…”
Section: Discussionmentioning
confidence: 71%
“…The nonlocal complex STR modified Korteweg-de Vries (mKdV) hierarchies via nonlocal symmetry reductions of matrix spectral problems was explored with their soliton solutions by the IST in [14]. Exact periodic and localized solutions of a nonlocal STR-Mel'nikov equation were derived by the HBM [15]. In [16], time reverse modeling was applied to localize and characterize acoustic emission using a numerical concrete model with a method for exploration of geophysics to nondestructive testing.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the Mel'nikov equation [27], researchers proposed the nonlocal Mel'nikov equation [28,29] where ò = ± 1, * represents complex conjugation. This equation describes the interaction of long wave with short-wave packets, and can be considered as a generalization of the Kadomtsev-Petviashvili (KP) equation [19].…”
Section: Introductionmentioning
confidence: 99%
“…Soliton and semi-rational solutions of equation (1) have been studied in [28] and the KP hierarchy reduction method is applied to construct Gram-type solutions of equation (1) in [30].…”
Section: Introductionmentioning
confidence: 99%